Building a better normal : visions of schools of education in a post-pandemic world - Goel, Priya; Simmons, Jonathan; Marwah, Smridhi; Andersson, Lars; Neuhaus, Sinikka; Mahat, Marian (Great debates in higher education., 2024)
The global COVID-19 pandemic fundamentally changed education as we know it. Globally, billions of learners at all levels were affected by months of rolling school closures and other severe pandemic restrictions to daily life. Magnifying issues of educational equity, access, and opportunity, this unprecedented global crisis forced Deans, and academic and professional staff in schools of education to make decisions for learning, teaching, research, and engagement in a fast-changing landscape. These decisions reshaped schools of education and the lives and experiences of staff and students in powerful ways. Building a Better Normal captures education scholars'reflections on the decision-making and impacts of their experiences from 2020 to 2023. Uniquely, the volume brings together Education Deans and scholars from Universitas 21 institutions. Drawing on case studies and narrative reflections, the contributors offer crucial insights that can guide higher education and schools of education on structural and conceptual shifts in approaches to leadership, research, teaching, learning, and student and staff well-being. The COVID-19 pandemic is a generation-defining event that will echo in the actions of teachers and researchers for years, allowing us to redefine the landscape of education for a better normal.